PARA UMA EDUCAÇÃO INCLUSIVA: TECNOLOGIAS DIGITAIS DA INFORMAÇÃO E COMUNICAÇÃO - Aline Regina de Souza Barros (2023)
The present research had as general objective to understand how the internal documents - Pedagogical Political Project (PPP) of EMEF Profa. Júlia Roseira Jerônimo, in Ouro Verde, state of São Paulo, and in the Annual Plans of teachers who taught in the third year of this same school, in 2019 - consider the use of TDIC, for an inclusive education that considers diversities in the training context of the classroom. The theoretical references are in the fields of Inclusive Education and discussions about how they approach the issues of diversities in a broader way, in particular: “Race”, Ethnicity, Gender, Childhoods and Disabilities, in addition to those that contemplate DICT. The research was baesd on documental analysis. Motivated by contemporary changes in face of technological innovations and inclusive education, it is important that new ways of teaching and learning are present in the schools, exploring resources that can contribute to advances in education and to the formation of a society that seeks equity in treatment with people and that enable equal opportunities. From the analysis of the documents, we registered the absence of the dimensions of those diversities considered as categories in this study. They do not appear in a specific way. Categories of people with disabilities, black people and women are not present in the PPP nor in the Planning. There is a concern with the insertion of students in a digital culture, through a specific project of the Computer Room, where the insertion of the student in the world of technologies is a goal, but without a concern for this as a propeller of an Inclusive Education, considering the diversities in the classroom. Therefore, the research identified the need for further research to generate analyses of the use of TDIC for an inclusive education with other perpectives, so that knowledge increasingly approaches all people involved in the teaching and learning processes.